The Figure of Luther in its Historical Context - Lazcano, Rafael (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Luther in its political, social, cultural and religious context. Educated in an atmosphere of austerity, religiosity and study, the doctor of Arts, of prodigious mind, intense spiritual life and unique ability to seek, find and do the will of God, entered the Augustinians of Erfurt to devote himself to preaching, study and teaching from the Chair of Sacred Scripture at the University of Wittenberg. The doctrine discovered, at the beginning in an embryonic way, according to which man attains justification-salvation by faith alone (sola fide), without need of works, will mark his work as an exegete, preacher, translator of the Bible and writer, activity maintained until the end with the publication of the controversial works against Rome and the Jews. After 500 years of the 95 theses on indulgences (1517), the figure of Luther, saved the distances, appears as a (prophetic) sign of the times and witness of the Gospel.